Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt Prestasi Retail Innovation Jakarta Barat - Erisa Aprina; Indri Indirasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to determine the positive and significant influence of motivation variables on employee performance, to determine the positive and significant influence of discipline variables on employee performance and to determine the positive and significant influence of motivation and discipline variables simultaneously on employee performance at PT Prestasi Retail Innovation West Jakarta. The sample used is a saturated sample technique totaling 63 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test and f-test. The results of the study show that: (1) Partially there is a positive and significant influence between compensation and employee performance at PT Prestasi Retail Innovation West Jakarta, this can be proven from the simple linear regression equation Y = 9,776 + 0,0,786 X₁ and thitung 3,360 > ttabel l 1,67022 with a significance of 0,001 < 0,05 (2) Partially, there is a positive and significant influence between discipline and employee performance at PT Prestasi Retail Innovation West Jakarta. This can be proven from the simple linear regression equation Y = 16,983 + 0,631 X₂ and the value of thitung 4,337 > ttabel1,67022 with a significance of 0,000 < 0.05 (3) Simultaneously, there is a positive and significant influence between motivation and employee performance at PT Prestasi Retail Innovation West Jakarta, this can be proven from the multiple linear regression equation Y = 6,672 + 0,433 X₁ + 0,423 X₂, a correlation value of 0,758 a determination coefficient value of 57,5%, and a value of fℎ???????????????????? 40,539 >f tabel 3,15 with a significance level of 0.000 < 0,05